Nucleic Acid-Based Approaches for Tumor Therapy - Hager, Simone (Cells, 2020)
Within the last decade, the introduction of checkpoint inhibitors proposed to boost the patients’ anti-tumor immune response has proven the efficacy of immunotherapeutic approaches for tumor therapy. Furthermore, especially in the context of the development of biocompatible, cell type targeting nano-carriers, nucleic acid-based drugs aimed to initiate and to enhance anti-tumor responses have come of age. This review intends to provide a comprehensive overview of the current state of the therapeutic use of nucleic acids for cancer treatment on various levels, comprising (i) mRNA and DNA-based vaccines to be expressed by antigen presenting cells evoking sustained anti-tumor T cell responses, (ii) molecular adjuvants, (iii) strategies to inhibit/reprogram tumor-induced regulatory immune cells e.g., by RNA interference (RNAi), (iv) genetically tailored T cells and natural killer cells to directly recognize tumor antigens, and (v) killing of tumor cells, and reprograming of constituents of the tumor microenvironment by gene transfer and RNAi. Aside from further improvements of individual nucleic acid-based drugs, the major perspective for successful cancer therapy will be combination treatments employing conventional regimens as well as immunotherapeutics like checkpoint inhibitors and nucleic acid-based drugs, each acting on several levels to adequately counter-act tumor immune evasion.